KAJIAN HARGA POKOK PRODUKSI OIL BURNER MOTIF BURUNG SEBAGAI BAHAN PERTIMBANGAN BISNIS IKM KERAMIK - I Nyoman Normal (Forum Manajemen STIMI Handayani Denpasar, 2017)
The aims of this research that relate design service of oil burner that bird motiff (d9,7-t8,0) were: 1) to calculate cost of good manufactured, 2) to determine cost price feasebly, and 3) to give justification to medium small industries of ceramic. Research results shew that: 1) the cost of good manufactured design service of oil burner that bird motiff (d9,7-t8,0) was Rp 46.836,05 each unit, 2) the cost price design service of oil burner that bird motiff (d9,7-t8,0) was Rp 60.886,86, and 3) The cost of good manufactured design service of oil burner that bird motiff (d9,7-t8,0) based on full cost use for medium small industries of ceramics as: a) evaluation tool of resources consumption into produce ceramics creative design, b) information material to know the structure of cost production about ceramic creative design, c) decision making base to buy and self produce ceramics creative design, d) cost price determination base about ceramics creative design, e) decreasing tool to production cost wasting about ceramic creative design for non-value added activities, f) information material to improve competence of ceramic creative design into result profit by monitor product life cycle cost, g) information material to planning, controlling, and decision making about product life cycle cost, h) cost reimbursement base about ceramic creative design, and i) the component of inventory costingabout ceramic creative design.